Degree of service-orientation in the pulp and paper industry. (6th January 2009) - Davidsson, Nina; Edvardsson, Bo; Gustafsson, Anders; Witell, Lars
Many companies in the process industries are seeing the advantages of services but are struggling with the changes these require as regards the offering and the organisation. This paper presents an empirical investigation within the pulp and paper industry based on a survey of Swedish manufacturing firms and a multiple case study of three case companies and their customers. To investigate whether the manufacturers active in this industry are product-oriented or are becoming more service-oriented, five themes important to the companies under study are presented and discussed: that is, finding the right mix of physical products and services, the concept of service, business models, technology-based services and organising service delivery.